2017
DOI: 10.1002/jcb.25775
|View full text |Cite
|
Sign up to set email alerts
|

GLUL Promotes Cell Proliferation in Breast Cancer

Abstract: Glutamate-ammonia ligase (GLUL) belongs to the glutamine synthetase family. It catalyzes the synthesis of glutamine from glutamate and ammonia in an ATP-dependent reaction. Here, we found higher expression of GLUL in the breast cancer patients was associated with larger tumor size and higher level of HER2 expression. In addition, GLUL was heterogeneously expressed in various breast cancer cells. The mRNA and protein expression levels of GLUL in SK-BR-3 cells were obviously higher than that in the other types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Meanwhile, we found an increased GLUL expression in all subtypes of lung cancer. Elevated GLUL has already been found in many other types of cancers (Christa et al, 1994;Rosati et al, 2013;Wang et al, 2016). Our results indicate that GLUL may also play some important roles in lung cancer progression.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Meanwhile, we found an increased GLUL expression in all subtypes of lung cancer. Elevated GLUL has already been found in many other types of cancers (Christa et al, 1994;Rosati et al, 2013;Wang et al, 2016). Our results indicate that GLUL may also play some important roles in lung cancer progression.…”
Section: Discussionsupporting
confidence: 76%
“…It is majorly expressed in normal muscle tissue, adipose tissue, the brain, and the liver to balance ammonia, glutamate, and glutamine levels in those organs and the whole body (Curthoys and Watford, 1995). The expression of GLUL is relatively low in other normal tissues but was found to be elevated in cancer cells from the liver, brain, and breasts (Christa et al, 1994;Rosati et al, 2013;Wang et al, 2016). Since GLUL is the only glutamine synthetase in the human body, most studies focus on its functions in benefiting cancer cells' survival and growth under glutamine restriction.…”
Section: Introductionmentioning
confidence: 99%
“…We found higher expression of GLUL in the breast cancer patients was associated with larger tumor size and higher level of HER2 expression . Great interest in GLUL research has led to discovery of several GLUL inhibitors.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, a mouse NSCLC model did not catabolize glutamine through glutaminolysis at all but depended solely on glucose-derived carbon flux [37]. Several studies have revealed a prognostic value of GLUL expression in different cancer types [21][22][23][24]. Further, the ablation of GLUL in SK-BR-3 cells reduced their proliferation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GLUL could be important beyond its main catalytic activity during tumor growth [20]. Increased GLUL expression has been reported as an early marker of hepatocellular carcinoma [21], promoting breast cancer cell proliferation [22], and also found to be an unfavorable prognostic marker in patients with glioblastoma multiforme (GBM) and ovarian cancer [23,24]. Our group has previously identified reduced GLUL transcription to be associated with resistance to the chemotherapeutic agent daunorubicin in clones of acute lymphoblastic leukemia (ALL) [14].…”
Section: Introductionmentioning
confidence: 99%